Wise words from across space and time : the official quotable Doctor Who - Scott, Cavan (Harper Design, 2014)
Over the years, Doctor Who has become one of the most popular science fiction series to date, with an ever growing and extremely dedicated fan base. Now fans can enjoy a plethora of their favorite memorable quotes and wisest words spoken throughout the series from the first episode to the most recent season starring Matt Smith. Each chapter focuses on a reoccurring theme or subject from the series.